Informative voting and the Samuelson rule - Felix Bierbrauer; Marco Sahm (Max Planck Institute for Research on Collective Goods, 2006)
We study the classical free-rider problem in public goods provision in a large economy with uncertainty about the average valuation of the public good. Individual preferences over public goods are shaped by a skill and a taste parameter. We use a mechanism design approach to solve for the optimal utilitarian provision rule. The relevant incentive constraints for information aggregation ensure that individuals behave as if they were engaging in informative voting over the level of public good provision. It is shown that the use of information by an optimal provision rule is inversely related to the polarization of preferences which results from the properties of the skill distribution.
Keywords: H41; D71; D72; D82; 330; information aggregation; informative voting; public goods; two-dimensional heterogeneity; Informationsverhalten; Öffentliches Gut; Trittbrettfahrerverhalten; Theorie